[Bożonarodzeniowa karta okolicznościowa z 1985 r. z foto-kolażem] . Christmas greeting card from 1985 with a photo-collage (Polska, 1985)
B&w print on white paper, with undivided back. Photographic collage. Christmas greeting card contains a photographic collage which represents the Holy Family surrounded by Lech Wałęsa, rev. Jerzy Popiełuszko and a anonymous group with Solidarity banner.